2006
DOI: 10.1016/s0022-5347(05)00061-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bowel for Ureteral Replacement for Complex Ureteral Reconstruction: Long-Term Results

Abstract: During long-term followup major complications are rare and renal function remains preserved. Ileal and intestinal ureteral substitution remains a safe and efficacious procedure in patients with complex and difficult ureteral issues not amenable to more conservative measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 11 publications
2
59
1
7
Order By: Relevance
“…However, we counsel patients preoperatively that the complication rate ranges from about 30 to 50%-minor mostly and major less often. Chung and colleagues followed patients for 6 years and found a complication rate of 28% (16 of 56 patients) in one series, with complications ranging from minor transient acidosis and pyelonephritis to permanent renal failure requiring nephrectomy [11]. Wolff et al found that 9 of 17 patients suffered from a complication during a mean followup time of about 15 years [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, we counsel patients preoperatively that the complication rate ranges from about 30 to 50%-minor mostly and major less often. Chung and colleagues followed patients for 6 years and found a complication rate of 28% (16 of 56 patients) in one series, with complications ranging from minor transient acidosis and pyelonephritis to permanent renal failure requiring nephrectomy [11]. Wolff et al found that 9 of 17 patients suffered from a complication during a mean followup time of about 15 years [12].…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, после открытой пла-стики мочеточника кишкой в 10% случаев наблю-даются такие отдаленные осложнения, как негер-метичность анастомоза, стриктура и фистула [2][3][4].…”
Section: оригинальные статьиunclassified
“…В этих случаях даже при открытом доступе встре-чаются технические сложности по выделению ки-шечника из спаек, его резекции и формированию анастомозов. Показанием к лапароскопической илеоуретеропластике в большинстве случаев были травмы мочеточников во время эндоскопических и гинекологических вмешательств, постлучевые и туберкулезной этиологии стриктуры мочеточника, его дефект после резекции по поводу опухоли [1,2,11,12]. У этих больных ввиду отсутствия спаечной болезни целесообразно выполнить кишечную пла-стику лапароскопическим доступом.…”
Section: оригинальные статьиunclassified
See 1 more Smart Citation
“…Für dieses Verfahren sind in der Literatur gute Langzeitergebnisse hinsichtlich Harnabfluss und Erhalt der Nierenfunktion belegt. Die Effizienz dieser Technik wurde in mehreren offen operativen Serien [13,14,15,16] und bislang auch kleinen laparoskopischen Serien belegt [17,18]. Bei ausreichender prä-operativer Nierenfunktion besteht ein nur sehr geringes Risiko hinsichtlich Störun-gen des Säure-Basen-Haushalts.…”
Section: Verwendung Tubularisiert Belassener Dünndarmsegmenteunclassified